Quantitative tourism industry analysis : - Hara, Tadayuki (Butterworth-Heinemann, 2008)
Quantitative Tourism Industry Analysis is the first book to deal with the input-output, social accounting matrix in a way which readers from a non-economics or non-mathematical background can follow, in order to understand how useful their application would be for tourism industry analysis. It acquaints readers with useful applications of economic modelling without the unnecessary burden of higher algebra, so that they will understand concepts of the economics measurement system, Tourism Satellite Accounts (TSA) methodology.